Unveiling the sociodemographic and socioeconomic determinants of antenatal care utilization in Bangladesh: insights from the 2017–18 BDHS - Md. Mojammel Haque Sakib; Muhammad Khairul Alam; Nilufar Yasmin; Rumana Rois (Journal of Health, Population and Nutrition)
Abstract Background Antenatal care (ANC) is indispensable for supervising and enhancing the health of both the mother and the baby during pregnancy. It helps to reduce the risks of complications and ensures better pregnancy outcomes. This study investigates the aspects that influence antenatal care (ANC) visits in Bangladesh, focusing on sociodemographic and socioeconomic factors. Methods The study used nationally representative data from the 2017–18 Bangladesh Demographic and Health Survey. Mann–Whitney and Kruskal–Wallis tests were conducted for bivariate analysis. The Boruta algorithm was utilized for variable selection. After employing various regression models, including Poisson Regression, Negative Binomial Regression, Zero-inflated Poisson Regression, and Zero-inflated Negative Binomial Regression (ZINB), we evaluated their performance and selected Zero-inflated Negative Binomial Regression (ZINB) for parameter estimation and interpretation. Results Our results reveal that less than 50% of women meet the WHO-recommended minimum of four ANC visits. Rural women were 12% less likely than urban women to receive antenatal care (ANC) visits, indicating an urban–rural discrepancy. Women with secondary and higher education levels were significantly more likely to have frequent visits, with incidence rate ratios (IRRs) of 1.27 (95% CI: 1.14–1.42) and 1.34 (95% CI: 1.18–1.51), respectively. Similarly, women from households with rich wealth status (IRR: 1.14, 95% CI: 1.08–1.21) and those exposed to media coverage (IRR: 1.19, 95% CI: 1.14–1.25) were more likely to attend frequent ANC visits. Conversely, women with higher birth order (IRR: 0.95 & 0.84, 95% CI: 0.90–1.00 & 0.76–0.92), unintentional pregnancy (IRR: 0.91 & 0.83, 95% CI: 0.86–0.96 & 0.77–0.91) were less likely to have ANC visits. Conclusion This study underscores a critical gap in ANC access, particularly among rural women, which poses challenges to achieving national and global maternal health targets. Addressing these disparities and making relevant policy implications such as expanding community-based ANC programs, integrating services into primary healthcare, and increasing awareness through mass media are required to enhance ANC accessibility and utilization in underserved populations.